2020
DOI: 10.1016/j.healun.2020.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A2A receptor agonist (regadenoson) in human lung transplantation

Abstract: BACKGROUND: Currently, there are no clinically approved treatments for ischemia-reperfusion injury after lung transplantation. Pre-clinical animal models have demonstrated a promising efficacy of adenosine 2A receptor (A 2A R) agonists as a treatment option for reducing ischemia-reperfusion injury. The purpose of this human study, is to conduct a Phase I clinical trial for evaluating the safety of continuous infusion of an A 2A R agonist in lung transplant recipients. METHODS: An adaptive, two-stage continual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…The use of azithromycin as prophylaxis for CLAD or as a rescue from BOS has been implemented by several institutions, as detailed previously with varying degrees of success (85-87, 90, 92). Also, an adenosine A2A receptor antagonist is under investigation to reduce invariant NKT cell mediated inflammation in PGD (173). Other strategies to dampen airway inflammation, such as regulatory T cell adoptive therapy and/or pretransplant allograft modification during ex vivo lung perfusion, have shown preclinical promise as adjuncts to traditional immune suppression (174).…”
Section: Discussionmentioning
confidence: 99%
“…The use of azithromycin as prophylaxis for CLAD or as a rescue from BOS has been implemented by several institutions, as detailed previously with varying degrees of success (85-87, 90, 92). Also, an adenosine A2A receptor antagonist is under investigation to reduce invariant NKT cell mediated inflammation in PGD (173). Other strategies to dampen airway inflammation, such as regulatory T cell adoptive therapy and/or pretransplant allograft modification during ex vivo lung perfusion, have shown preclinical promise as adjuncts to traditional immune suppression (174).…”
Section: Discussionmentioning
confidence: 99%
“…Selective adenosine A 2a receptor stimulation has been identified as a potential cytoprotective strategy to mitigate IRI in various settings, due to its well-documented anti-inflammatory effects [ 22 ]. Recently, Lau et al have published data on the effects of regadenoson, an adenosine A2a receptor agonist, in the setting of clinical lung transplantation [ 33 ]. In this pilot study of 14 lung transplantation recipients, the authors concluded that regadenoson can be safely infused in the setting of human lung transplantation with no dose-limiting toxicities or drug-related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the partial adenosine A1 receptor agonist neladenoson bialanate has been commonly used in chronic heart failure treatment ( 154 , 155 ). Adenosine A2A receptor agonist CGS21680 reduces the inflammatory response of lung transplantation ( 156 , 157 ) and liver transplantation ( 47 ). It can as well significantly reduce the infarct area of isolated perfused mouse hearts ( 48 ).…”
Section: Clinical Application and Prospectsmentioning
confidence: 99%